APPLICATION OF VIRTUAL LABORATORY WORK ON HEAT TREATMENT OF STEEL TO IMPROVE THE QUALITY OF TRAINING OF SPECIALISTS-MATERIAL SCIENTISTS - Нovorun Tetiana; Berladir Кhrystyna; Belous , Olena; Khaniukov , Kyrylo; Varakin , Vitaly (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
The article describes the main principles of creating and using the virtual laboratory work «Thermal treatment of carbon steels», developed for materials science students. The stages of conducting virtual laboratory work on various types of heat treatment are considered in detail. A mandatory element of virtual laboratory work is an interactive environment of interaction with students, which ensures constant monitoring of knowledge on the topic and object of research being studied.